Eulogy for Georg Bredig (1944)
A piece was written to honor Georg Bredig (1868-1944) after his passing on April 25, 1944. The contents of the letter praise Bredig as a person, teacher, and scientist. He is described as a passionate champion of democracy, international law, and peace. While the author of this letter is unknown, it is clear they hold Georg in high regard.
Keywords: Bredig, Georg, 1868-1944; Chemists; College teachers; Eulogies